Delinking, food sovereignty, and populist agronomy: notes on an intellectual history of the peasant path in the global South. Issue 155 (2nd January 2018) - Ajl, Max
ABSTRACT: The article examines the weakness of discourses around food sovereignty in Southwest Asia and North Africa, and examines some older currents resembling the food sovereignty discourse. The author first historically situates the emergence of food sovereignty. He discusses agro-ecology – the 'technics' (or social embeddedness of technology) of food sovereignty – and its national-popular content, before then developing elements of the delinking paradigm. He goes on to discuss Tunisian national-popular and Third Worldist agronomists' and economists' efforts to develop technics and frameworks for food sovereignty in the 1970s and 1980s. The article compares the food sovereignty paradigm with auto-centred, self-reliant development proposals, and the proposals of the Tunisian economists and agronomists.